OF THE SERVICE LEVEL IN AN AIRCRAFT MAINTENANCE ORGANIZATION BY GROUP QUALITY INDICATORS - Melnyk, Volodymyr; Radko, Oleh; Yakymenko, Ilya; Vasylyk, Mykhailo (Problems of Friction and Wear, 2024)
The article presents the results of a comparative analysis of the assessment of the efficiency of three aviation enterprises: AVIATECH LLC, SPC MS AVIA-GRADE LLC and AIR SERVICE LLC by quality indicators. These organizations provide aircraft maintenance services. The average quality assessment in an aircraft maintenance organization is calculated as the arithmetic mean of group quality indicators for each maintenance organization. It is proposed to assess the level of service quality by an integral quality indicator. The integral indicator is the final indicator of the service quality, calculated on the basis of a set of quality assessments of various components of the processes of activity of aircraft maintenance organizations obtained in the process of monitoring.